Composition of carcinoecia formed by Stylobates sp. (Cnidaria: Anthozoa: Actiniidae), a sea anemone symbiotic with hermit crabs (Crustacea: Decapoda: Paguroidea) - Akihiro Yoshikawa; Shiori Nakazawa; Akira Asakura (PANGAEA, 2018)
Raw mass spectra acquired from the upper (band 1) and lower (band 2) bands of the intact (i) and reduced (r) conditions .